2011
DOI: 10.1097/ijg.0b013e3181f7afb8
|View full text |Cite
|
Sign up to set email alerts
|

Central Corneal Thickness and Corneal Curvature in Pseudoexfoliation Syndrome With and Without Glaucoma

Abstract: CCT was significantly thinner in eyes with PES compared with control eyes; however, difference between the PEG and control eyes was insignificant. In addition, mean K readings were not different in study and control eyes. Thinner CCT in eyes with PES, both as it is an independent risk factor and as a result of artificially lower intraocular pressure readings, may be an illuminating cause for development and rapid progression of glaucoma in the patients with PES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 30 publications
4
16
1
3
Order By: Relevance
“…Ozcura et al showed that there was no significant change in CC in eyes with PXE compared with control eyes, [7] which is similar to the results obtained in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…Ozcura et al showed that there was no significant change in CC in eyes with PXE compared with control eyes, [7] which is similar to the results obtained in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…The researchers represented that the corneal endothelial cell density and CCT were significantly lower in the PXS eyes than in the control eyes, but there were no significant differences in these factors between the PXS eyes in patients with and without glaucoma. Ozcura et al (27) reported that CCT was significantly thinner in eyes with PXS than in control eyes, but was not thinner in the eyes of those with pseudoexfoliative glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…12 Birçok çalışmada, DM ile MKK arasında bir ilişki olduğu belirtilmiştir. [13][14][15] Özcura ve ark., Tip 2 DM'li hastaların MKK'lerinin kontrol grubuna göre daha yüksek olduğunu bildirdikleri çalışmalarında, MKK'deki artışın DM'nin süresiyle ve DR varlığı ile ilişki göstermediğini belirtmişlerdir.…”
Section: Gereç Ve Yöntemlerunclassified
“…[13][14][15]19 Çalışmamızda, diyabetli gözlerde MKK'nin kontrol grubuna göre yüksek olduğunu saptadık. Lee ve ark., DM'li grupta MKK'nın endotel fonksiyon bozukluğu sonucu oluşan hidrasyona bağlı olarak daha kalın olduğunu bildirmişlerdir.…”
Section: İstati̇sti̇ksel Anali̇zunclassified